Denetimli serbestlik sürecindeki suça sürüklenen ergenlerde sosyal dışlanma, toplumsal aidiyet ve gelecek beklentisinin incelenmesi - Süzer Gamlı, İpek and Karakuş, Oğuz Bilal and Adak, İbrahim and Yaşöz, Cemre (Journal of Dependence, 2024)
Objective: The aim of this study was to compare social exclusion, sense of community and future expectation in adolescents who are in probation due to substance use or supply with healthy controls. Method: Seventy adolescents who applied to Child Alcohol and Drug Addiction Treatment Center in Istanbul as probation due to drug use or supply, and 70 age, gender and socioeconomic level matched controls without psychiatric diagnosis were included in the study. Sociodemographic form, adolescent social exclusion (ostracism) scale, adolescent sense of community scale and adolescent future expectations scale were applied. Results: Among adolescents under probation, 85.7% (n=60) were male and the mean age was 17.17 ± 0.85. Among those, 74.3% (n=52) had a psychiatric illness. The most common disorder was attention deficit hyperactivity disorder (ADHD) with a rate of 80.2%. School discontinuation and family forensic history were significantly higher in the probation group. In the probation sample, the social exclusion scores were significantly higher, whereas sense of community and future expectation scores were significantly lower). Conclusion: Substance use can affect social exclusion, sense of community and future expectations. It is essential to examine psychopathologies including ADHD and psychosocial factors and identify risky groups in adolescent in the probation sample.